ISCHEMIA Trial: Key Questions and Answers - Jose Lopez-Sendon; Raúl Moreno; Juan Tamargo (European Cardiology Review)
A healthy lifestyle, myocardial revascularisation and medical therapy constitute the three pillars for the treatment of ischaemic heart disease. Lifestyle and optimal medical therapy should be used in all cases. However, the selection of cases for revascularisation among stable patients remains controversial. The ISCHEMIA trial compared an early invasive strategy with revascularisation plus optimal medical therapy against initial optimal medical therapy alone with revascularisation reserved for cases in which symptom control was insufficient. The study included over 5,000 patients with stable coronary artery disease and moderate to severe myocardial ischaemia. No differences were found in relevant clinical outcomes, including all-cause mortality, cardiovascular death, MI, heart failure and stroke, over a follow-up of 3.2 years. Conversely, angina control was better in patients with severe symptomatic angina. Following the tradition of all trials comparing medical therapy alone with revascularisation, the ISCHEMIA trial results are controversial, but an analysis of the design and results of the trial offers important information to better understand, evaluate and treat the growing number of patients with stable chronic ischaemic heart disease and moderate to severe myocardial ischaemia.